Real time control of water distribution networks: A state-of-the-art review. (15th September 2019) - Creaco, E.; Campisano, A.; Fontana, N.; Marini, G.; Page, P.R.; Walski, T.
Abstract: This paper presents a review of the current state of the art of real time control (RTC) of water distribution networks (WDNs). After proving the basic concept and terms of RTC and presenting sensors, regulation devices and controllers typically used in WDNs, the paper goes on by describing the most frequent control objectives, which mainly include service pressure regulation, control of tank filling and energy production in each WDN district. Various control methodologies recently proposed in the scientific literature are presented and discussed, along with experimental and numerical results achieved. Also, aspects related to the cost-effectiveness of RTC are critically analyzed. The paper ends by giving an outlook into potential future developments in the area of RTC for WDNs. Graphical abstract: Image 1 Highlights: Real Time Control (RTC) in Water Distribution Networks (WDNs) has been reviewed. The fundamental concepts of RTC and the devices used in WDNs are presented. RTC of service pressure, tank level and electric energy production is described. The successful application of service pressure RTC to a real WDN is reported. Need of new experimental works to corroborate numerical findings obtained so far.